Positive plate as well as electrochemical device and electronic equipment comprising positive plate
By designing a multi-layer active material layer in the cathode sheet of the nickel-manganate battery, the average particle size of the nickel-manganate battery decreases in sequence along the direction away from the cathode current collector, the problem of high impedance and performance of the existing cathode materials of the nickel-manganate battery is solved, and low impedance and excellent high-temperature dynamic performance are achieved.
Patent Information
- Application Number
- CN202411878442.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
AI Technical Summary
The existing Ni-Manganese Lithium Manganese Battery cathode material has limited the wide application of Ni-Manganese Battery batteries due to the high impedance caused by large-particle single crystal Ni-Manganese Battery and the inability to take into account excellent kinetic performance and high-temperature gas production performance.
A positive electrode sheet is designed, which includes a multi-layer active material layer, and the average particle size of lithium nickel manganate is sequentially decreasing along the direction away from the positive electrode current collector, thereby reducing the impedance of the battery and improving the high temperature performance.
It has achieved low impedance and low high temperature gas production growth of lithium-ion batteries, and can take into account excellent high temperature performance and kinetic performance.
Smart Images

Figure CN119650585A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a positive electrode sheet and an electrochemical device and an electronic device containing the positive electrode sheet. Background Art
[0002] The rapid development of power batteries and electrochemical energy storage systems has put forward higher requirements for lithium-ion batteries, among which positive electrode materials are the key. The next generation of positive electrode materials should have the characteristics of high energy density, low cost and cobalt-free. Lithium nickel manganese oxide is an important development direction for the next generation of low-cost positive electrode materials due to its advantages such as low cost, simple synthesis process, cobalt-free raw materials, high voltage platform and three-dimensional ion diffusion channels.
[0003] However, existing lithium nickel manganese oxide batteries mostly use large-particle single-crystal lithium nickel manganese oxide, which has a long ion / electron transmission path and large impedance, and cannot take into account both excellent kinetic performance and high-temperature gas production performance, which hinders the large-scale entry of lithium nickel manganese oxide batteries into the market. Summary of the invention
[0004] In order to solve the above problems existing in the prior art when lithium nickel manganese oxide is used as a positive electrode material, the present invention provides a positive electrode sheet and an electrochemical device and an electronic device containing the same. The electrochemical device (especially a lithium ion battery) prepared using the positive electrode sheet has a low impedance and a low high-temperature gas production growth, and can take into account excellent high-temperature performance and kinetic performance.
[0005] To achieve the above objectives, the present invention adopts the following technical solutions.
[0006] In a first aspect, the present invention provides a positive electrode sheet comprising a positive electrode current collector and a positive electrode material layer, wherein the positive electrode material layer is arranged on at least one surface of the positive electrode current collector; the positive electrode material layer comprises at least two active material layers; the positive electrode material in each active material layer comprises lithium nickel manganese oxide; and the average particle size of the lithium nickel manganese oxide in each active material layer decreases successively in a direction away from the positive electrode current collector.
[0007] In a second aspect, the present invention provides an electrochemical device comprising the positive electrode sheet as described above.
[0008] In a third aspect, the present invention provides an electronic device comprising the electrochemical device as described above.
[0009] The positive and progressive effects of the present invention are:
[0010] The present invention is directed to a positive electrode sheet whose positive electrode material includes lithium nickel manganese oxide, and is specially designed such that the average particle size of lithium nickel manganese oxide in each active material layer of the positive electrode sheet decreases in sequence in the direction away from the positive electrode current collector. The electrochemical device (especially lithium ion battery) prepared by the positive electrode sheet has low impedance and low high-temperature gas production growth, and can take into account both excellent high-temperature performance and kinetic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 Schematic diagram of the structure of the positive electrode sheet obtained in Example 1-13.
[0012] Figure 2 This is a SEM image (part) of the longitudinal cross section of the positive electrode sheet obtained in Example 1.
[0013] Reference numerals:
[0014] Positive electrode current collector 1
[0015] First active material layer 2
[0016] Second active material layer 3 DETAILED DESCRIPTION
[0017] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0018] Positive electrode
[0019] In the positive electrode sheet provided in the first aspect of the present invention, it includes a positive electrode collector and a positive electrode material layer, the positive electrode material layer is arranged on at least one surface of the positive electrode collector; the positive electrode material layer includes at least two layers of active material layers; the positive electrode material in each layer of the active material layer includes lithium nickel manganese oxide; the average particle size of the lithium nickel manganese oxide in each layer of the active material layer decreases successively along the direction away from the positive electrode collector.
[0020] In the present invention, the average particle size of lithium nickel manganese oxide in each active material layer can be obtained by the following method: Scanning electron microscope (SEM) is used to scan the longitudinal section of the positive electrode sheet at a magnification of 5000 times, and a 25μm×15μm area is randomly selected in each active material layer in the obtained SEM image, and the particle size of all lithium nickel manganese oxide particles in the area is counted, and the average value is calculated, which is the average particle size of lithium nickel manganese oxide in the active material layer of the layer; wherein, the longitudinal section of the positive electrode sheet refers to the section along the thickness direction of the electrode sheet; the particle size of a single lithium nickel manganese oxide particle is the distance between the two farthest endpoints of the particle that do not overlap. When the active material layer of the layer also includes other positive electrode materials, different positive electrode material particles can be distinguished by means of EDS (Energy Dispersive Spectrometer) and the like.
[0021] Most of the existing batteries that use lithium nickel manganese oxide as the positive electrode material use large-particle single-crystal lithium nickel manganese oxide to reduce the electrode / electrolyte contact area, thereby reducing interfacial side reactions and reducing gas production. However, simply using large-particle single-crystal lithium nickel manganese oxide will increase the transmission path of electrons / ions. Furthermore, considering that the electronic conductivity of lithium nickel manganese oxide itself is poor, simply using large-particle single-crystal lithium nickel manganese oxide will seriously deteriorate the impedance of the lithium nickel manganese oxide battery. If the impedance is reduced by simply reducing the particle size, it will also bring about the problem of deterioration of high-temperature gas production, making it impossible to take into account both excellent rate performance and kinetic performance.
[0022] In the present invention, the molecular formula of the lithium nickel manganese oxide can be LiNi b Mn 2-b-a M a O 4 , 0≤a≤0.1, 0.3≤b≤0.7. For example, when a=0 and b=0.5, the molecular formula of the lithium nickel manganese oxide is LiNi 0.5 Mn 1.5 O 4 For another example, when a>0, preferably, 0.001≤a≤0.1, corresponding to the case where the lithium nickel manganese oxide contains a doping element M. M may include one or more of Co, Mg, Al, Cu, Ta, Zr, Ti and Ca.
[0023] In some embodiments, the positive electrode material in each active material layer further independently includes one or both of lithium iron manganese phosphate and lithium iron phosphate.
[0024] Wherein, the molecular formula of the lithium manganese iron phosphate can be LiMn c Fe 1-c PO 4 , c is 0.01-0.99, for example, 0.6.
[0025] The average particle size of the lithium manganese iron phosphate may be 0.1-0.5 μm, for example, 0.3 μm.
[0026] The average particle size of the lithium iron phosphate may be 1-1.3 μm, for example, 1.1 μm.
[0027] In some embodiments, along the direction away from the positive electrode current collector, the ratio of the average particle size of lithium nickel manganese oxide in two adjacent active material layers is (1.5-20):1, preferably (2-8):1, for example, 2.7:1, 3:1, 4:1, 5:1 or 6:1.
[0028] In some embodiments, the content of lithium nickel manganese oxide in each active material layer is greater than or equal to 80%, and the content of lithium nickel manganese oxide is the mass percentage of the mass of lithium nickel manganese oxide in a layer of the active material layer to the total mass of the positive electrode material in the active material layer.
[0029] In some embodiments, the total thickness of the positive electrode material layer is 10-100 μm, for example, 70 μm.
[0030] In the present invention, the thickness of each active material layer and the total thickness of the positive electrode material layer refer to the compaction of 3.0 g / cm 3 The thickness of the time.
[0031] In some embodiments, the active material layer also includes a conductive agent, and the content of the conductive agent in each active material layer increases successively in the direction away from the positive electrode current collector, and the content of the conductive agent is the mass percentage of the mass of the conductive agent in a layer of the active material layer to the total mass of the active material layer in that layer.
[0032] In the present invention, the conductive agent may be a conventional conductive material in the art, preferably including one or more of conductive carbon black (Super P, referred to as SP), acetylene black, carbon nanotubes (CNT), graphene and vapor grown carbon fiber reinforcement (VGCF).
[0033] In some embodiments, the active material layer further includes a binder.
[0034] In the present invention, the binder may be a binder commonly used in the art, preferably including one or both of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), such as PVDF.
[0035] In some embodiments, the content of the binder is 0.5%-3%, and the content of the binder is the mass percentage of the mass of the binder in a layer of the active material layer to the total mass of the active material layer.
[0036] In some embodiments, in each active material layer, the mass ratio of the positive electrode material, the conductive agent, and the binder is (80-99): (1.8-3.2): (0.5-3).
[0037] In some embodiments, the positive electrode material layer includes two active material layers, which are a first active material layer and a second active material layer in the direction away from the positive electrode current collector; the first active material layer includes a first positive electrode material; and the second active material layer includes a second positive electrode material.
[0038] In some preferred embodiments, the average particle size of lithium nickel manganese oxide in the first positive electrode material is 3-6 μm, for example, 4 μm or 5 μm.
[0039] In some preferred embodiments, the average particle size of lithium nickel manganese oxide in the second positive electrode material is 0.5-2 μm, for example, 1 μm or 1.5 μm.
[0040] In some preferred embodiments, in the first active material layer, the content of the first positive electrode material is 80%-99%, for example, 96.6%, 97.2% or 97.8%, where the percentage is the mass percentage of the first active material layer.
[0041] In some preferred embodiments, in the second active material layer, the content of the second positive electrode material is 80%-99%, for example, 95.8%, 96.6%, 97.2% or 97.8%, where the percentage is the mass percentage of the second active material layer.
[0042] In some preferred embodiments, the first active material layer includes a first conductive agent, and the second active material layer includes a second conductive agent.
[0043] In some more preferred embodiments, the content of the first conductive agent is the same as the content of the second conductive agent; or, the content of the first conductive agent is less than the content of the second conductive agent; wherein the content of the first conductive agent is the mass percentage of the first active material layer; and the content of the second conductive agent is the mass percentage of the second active material layer.
[0044] In some more preferred embodiments, the mass ratio of the first conductive agent to the second conductive agent is 1:(0.5-3), preferably 1:(1-3), and further preferably 1:(1.05-2).
[0045] In some more preferred embodiments, the content of the first conductive agent is 1.8%-3.2%, where the percentage is the mass percentage of the first active material layer.
[0046] In some more preferred embodiments, the content of the second conductive agent is 1.8%-3.2%, where the percentage is the mass percentage of the second active material layer.
[0047] In some preferred embodiments, the thickness ratio of the first active material layer to the second active material layer is 1:(0.5-10), preferably 1:(1.5-5), for example 1:1.
[0048] In some preferred embodiments, the positive electrode material layer includes two active material layers, which are the first active material layer and the second active material layer in the direction away from the positive electrode current collector; the first active material layer includes a first positive electrode material and a first conductive agent; the second active material layer includes a second positive electrode material and a second conductive agent; the first positive electrode material and the second positive electrode material include lithium nickel manganese oxide; the average particle size of lithium nickel manganese oxide in the first positive electrode material is 3-6 μm; the average particle size of lithium nickel manganese oxide in the second positive electrode material is 0.5-2 μm; the content of the first conductive agent is 1.8%-3.2%; the content of the second conductive agent is 1.8%-3.2%.
[0049] In some specific embodiments, the positive electrode material layer includes two active material layers, which are the first active material layer and the second active material layer in the direction away from the positive electrode current collector; the first active material layer includes a first positive electrode material and a first conductive agent; the second active material layer includes a second positive electrode material and a second conductive agent; the first positive electrode material and the second positive electrode material are lithium nickel manganese oxide; the average particle size of lithium nickel manganese oxide in the first positive electrode material is 4 μm; the average particle size of lithium nickel manganese oxide in the second positive electrode material is, for example, 2 μm, 1.5 μm, 1 μm or 0.5 μm; the content of the first conductive agent is 1.8%; the content of the second conductive agent is 1.8%.
[0050] In some specific embodiments, the positive electrode material layer includes two active material layers, which are the first active material layer and the second active material layer in the direction away from the positive electrode current collector; the first active material layer includes a first positive electrode material and a first conductive agent; the second active material layer includes a second positive electrode material and a second conductive agent; the first positive electrode material and the second positive electrode material are lithium nickel manganese oxide; the average particle size of lithium nickel manganese oxide in the first positive electrode material is, for example, 3 μm, 4 μm, 5 μm or 6 μm; the average particle size of lithium nickel manganese oxide in the second positive electrode material is 1 μm; the content of the first conductive agent is 1.8%; the content of the second conductive agent is 3.2%.
[0051] In a specific embodiment, the positive electrode material layer includes two active material layers, which are the first active material layer and the second active material layer in the direction away from the positive electrode current collector; the first active material layer includes a first positive electrode material and a first conductive agent; the second active material layer includes a second positive electrode material and a second conductive agent; the first positive electrode material and the second positive electrode material are lithium nickel manganese oxide and lithium iron manganese phosphate; the mass ratio of lithium nickel manganese oxide and lithium iron manganese phosphate is 95:5; the average particle size of lithium nickel manganese oxide in the first positive electrode material is 4 μm; the average particle size of lithium nickel manganese oxide in the second positive electrode material is 2 μm; the content of the first conductive agent is 1.8%; the content of the second conductive agent is 1.8%.
[0052] In a specific embodiment, the positive electrode material layer includes two active material layers, which are the first active material layer and the second active material layer in the direction away from the positive electrode current collector; the first active material layer includes a first positive electrode material and a first conductive agent; the second active material layer includes a second positive electrode material and a second conductive agent; the first positive electrode material and the second positive electrode material are lithium nickel manganese oxide and lithium iron phosphate; the mass ratio of lithium nickel manganese oxide and lithium iron phosphate is 95:5; the average particle size of lithium nickel manganese oxide in the first positive electrode material is 4 μm; the average particle size of lithium nickel manganese oxide in the second positive electrode material is 2 μm; the content of the first conductive agent is 1.8%; the content of the second conductive agent is 1.8%.
[0053] In a specific embodiment, the positive electrode material layer includes two active material layers, which are the first active material layer and the second active material layer in the direction away from the positive electrode current collector; the first active material layer includes a first positive electrode material and a first conductive agent; the second active material layer includes a second positive electrode material and a second conductive agent; the first positive electrode material and the second positive electrode material are lithium nickel manganese oxide; the average particle size of lithium nickel manganese oxide in the first positive electrode material is 4 μm; the average particle size of lithium nickel manganese oxide in the second positive electrode material is 2 μm; the content of the first conductive agent is 1.2%; the content of the second conductive agent is 2.4%.
[0054] In a specific embodiment, the positive electrode material layer includes two active material layers, which are the first active material layer and the second active material layer in the direction away from the positive electrode current collector; the first active material layer includes a first positive electrode material and a first conductive agent; the second active material layer includes a second positive electrode material and a second conductive agent; the first positive electrode material and the second positive electrode material are lithium nickel manganese oxide; the average particle size of lithium nickel manganese oxide in the first positive electrode material is 4 μm; the average particle size of lithium nickel manganese oxide in the second positive electrode material is 2 μm; the content of the first conductive agent is 2.4%; the content of the second conductive agent is 1.2%.
[0055] In some preferred embodiments, the method for preparing the positive electrode sheet comprises the following steps: a first positive electrode slurry obtained by fully stirring and mixing the components of the first active material layer in a solvent is coated on at least one surface of the positive electrode collector, and dried, so that the first positive electrode slurry forms a first active material layer; a second positive electrode slurry obtained by fully stirring and mixing the components of the second active material layer in a solvent is coated on the surface of the first active material layer, and dried, so that the second positive electrode slurry forms a second active material layer; and cold pressing and slitting are performed to obtain the product.
[0056] In some preferred embodiments, the positive electrode material layer includes three active material layers, which are, in order, a first active material layer, a second active material layer and a third active material layer along the direction away from the positive electrode current collector; the first active material layer includes a first positive electrode material; the second active material layer includes a second positive electrode material; and the third active material layer includes a third positive electrode material.
[0057] In some more preferred embodiments, the average particle size of lithium nickel manganese oxide in the first positive electrode material is 3-6 μm, for example, 4 μm.
[0058] In some more preferred embodiments, the average particle size of lithium nickel manganese oxide in the second positive electrode material is 0.5-2 μm, for example, 2 μm.
[0059] In some more preferred embodiments, the average particle size of lithium nickel manganese oxide in the third positive electrode material is 0.5-2 μm, for example, 1 μm.
[0060] In some more preferred embodiments, in the first active material layer, the content of the first positive electrode material is 80%-99%, for example, 97.2%, where the percentage is the mass percentage of the first active material layer.
[0061] In some more preferred embodiments, in the second active material layer, the content of the second positive electrode material is 80%-99%, for example, 97.2%, where the percentage is the mass percentage of the second active material layer.
[0062] In some more preferred embodiments, in the third active material layer, the content of the third positive electrode material is 80%-99%, for example, 97.2%, where the percentage is the mass percentage of the third active material layer.
[0063] In some preferred embodiments, the first active material layer includes a first conductive agent, the second active material layer includes a second conductive agent, and the third active material layer includes a third conductive agent.
[0064] In some more preferred embodiments, the content of the first conductive agent is the same as the content of the second conductive agent; or, the content of the first conductive agent is less than the content of the second conductive agent; wherein the content of the first conductive agent is the mass percentage of the first active material layer; and the content of the second conductive agent is the mass percentage of the second active material layer.
[0065] In some more preferred embodiments, the content of the second conductive agent is the same as the content of the third conductive agent; or, the content of the second conductive agent is less than the content of the third conductive agent; wherein the content of the second conductive agent is the mass percentage of the second active material layer; and the content of the third conductive agent is the mass percentage of the third active material layer.
[0066] In some more preferred embodiments, the mass ratio of the first conductive agent to the second conductive agent is 1:(0.5-3), preferably 1:(1-3), and further preferably 1:(1.05-2).
[0067] In some more preferred embodiments, the mass ratio of the second conductive agent to the third conductive agent is 1:(0.5-3), preferably 1:(1-3), and further preferably 1:(1.05-2).
[0068] In some more preferred embodiments, the content of the first conductive agent is 1.8%-3.2%, where the percentage is the mass percentage of the first active material layer.
[0069] In some more preferred embodiments, the content of the second conductive agent is 1.8%-3.2%, where the percentage is the mass percentage of the second active material layer.
[0070] In some more preferred embodiments, the content of the third conductive agent is 1.8%-3.2%, where the percentage is the mass percentage of the third active material layer.
[0071] In some more preferred embodiments, the thickness ratio of the first active material layer to the second active material layer is 1:(0.5-10), preferably 1:(1.5-5), for example 1:0.5.
[0072] In some more preferred embodiments, the thickness ratio of the second active material layer to the third active material layer is 1:(0.5-10), more preferably 1:(1.5-5), for example 1:1.
[0073] In some more preferred embodiments, the positive electrode material layer includes three active material layers, which are the first active material layer, the second active material layer and the third active material layer in the direction away from the positive electrode current collector; the first active material layer includes a first positive electrode material and a first conductive agent; the second active material layer includes a second positive electrode material and a second conductive agent; the third active material layer includes a third positive electrode material and a third conductive agent; the first positive electrode material, the second positive electrode material and the third positive electrode material include lithium nickel manganese oxide; the average particle size of lithium nickel manganese oxide in the first positive electrode material is 3-6 μm; the average particle size of lithium nickel manganese oxide in the second positive electrode material is 0.5-2 μm; the average particle size of lithium nickel manganese oxide in the third positive electrode material is 0.5-2 μm; the content of the first conductive agent is 1.8%-3.2%; the content of the second conductive agent is 1.8%-3.2%; the content of the third conductive agent is 1.8%-3.2%.
[0074] In a specific embodiment, the positive electrode material layer includes three active material layers, which are the first active material layer, the second active material layer and the third active material layer in the direction away from the positive electrode current collector; the first active material layer includes a first positive electrode material and a first conductive agent; the second active material layer includes a second positive electrode material and a second conductive agent; the third active material layer includes a third positive electrode material and a third conductive agent; the first positive electrode material, the second positive electrode material and the third positive electrode material are lithium nickel manganese oxide; the average particle size of lithium nickel manganese oxide in the first positive electrode material is 4 μm; the average particle size of lithium nickel manganese oxide in the second positive electrode material is 2 μm; the average particle size of lithium nickel manganese oxide in the third positive electrode material is 1 μm; the content of the first conductive agent is 1.8%; the content of the second conductive agent is 1.8%; the content of the third conductive agent is 1.8%.
[0075] In some preferred embodiments, the preparation method of the positive electrode sheet comprises the following steps: coating a first positive electrode slurry obtained by fully stirring and mixing the components of the first active material layer in a solvent on at least one surface of the positive electrode collector, and drying, wherein the first positive electrode slurry forms a first active material layer; coating a second positive electrode slurry obtained by fully stirring and mixing the components of the second active material layer in a solvent on the surface of the first active material layer, and drying, wherein the second positive electrode slurry forms a second active material layer; coating a third positive electrode slurry obtained by fully stirring and mixing the components of the third active material layer in a solvent on the surface of the second active material layer, and drying, wherein the third positive electrode slurry forms a third active material layer; cold pressing, and slitting to obtain.
[0076] Electrochemical Devices
[0077] In the electrochemical device provided in the second aspect of the present invention, it includes the positive electrode sheet as described above.
[0078] In the present invention, the electrochemical device is preferably a battery.
[0079] In an optional embodiment, the electrochemical device is a lithium ion battery; the lithium ion battery further comprises a negative electrode sheet, a separator and an electrolyte.
[0080] Negative plate
[0081] In the present invention, the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer, and the negative electrode material layer is disposed on at least one surface of the negative electrode current collector.
[0082] In the present invention, the negative electrode material in the negative electrode material layer can be a negative electrode material conventionally used in the art, preferably including one or more of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase carbon microbeads, silicon dioxide and silicon-carbon materials, such as artificial graphite.
[0083] In some embodiments, the negative electrode material layer further includes a thickener.
[0084] The addition of the thickener can increase the system viscosity of each component in the negative electrode slurry, and can be a thickener conventionally used in the art for preparing negative electrode sheets, such as sodium carboxymethyl cellulose (CMC).
[0085] In some embodiments, the negative electrode material layer further includes a conductive agent.
[0086] There are no particular restrictions on the conductive agent, as long as it has conductivity and does not cause chemical changes in the battery. For example, the conductive agent may be: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as conductive carbon black (Super P, referred to as SP), carbon nanotubes (CNT), acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black or carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum or silver; conductive whiskers, such as zinc oxide whiskers or potassium titanate whiskers; conductive metal oxides, such as titanium dioxide; or conductive polymers, such as polyphenylene derivatives.
[0087] In some specific embodiments, the conductive agent in the negative electrode material layer is acetylene black.
[0088] In some embodiments, the negative electrode material layer further includes a binder.
[0089] The type of the binder is not particularly limited, and can be selected from polyvinylidene fluoride, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid (PAA), ethylene-propylene-diene terpolymer and its sulfonate, styrene-butadiene rubber (SBR), fluororubber and various copolymers, such as SBR.
[0090] In some specific embodiments, in the negative electrode material layer, the mass ratio of the negative electrode material, the conductive agent, the binder and the thickener is 96.4:1:1.4:1.2.
[0091] In the present invention, the negative electrode current collector may be a conventional negative electrode current collector in the art. The negative electrode current collector is used as a substrate to support the negative electrode material layer, and is generally a metal foil having a thickness of 3-500 microns. There is no particular restriction on the material, as long as it has high conductivity and does not produce chemical reactions in the secondary battery system. For example, it can be a foil formed after surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel, carbon, etc. The negative electrode current collector is generally a smooth surface, but fine lines may also be formed on its surface to increase the adhesion between the negative electrode material layer and the current collector. In addition to the foil, the negative electrode current collector may also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. Generally, the negative electrode current collector is copper foil.
[0092] In some embodiments, the method for preparing the negative electrode sheet comprises the following steps: thoroughly stirring and mixing the components of the negative electrode material layer in a solvent to obtain a negative electrode slurry which is applied on at least one surface of the negative electrode current collector, dried, cold pressed, and cut.
[0093] Diaphragm
[0094] In the present invention, the diaphragm may be a diaphragm conventionally used in the art.
[0095] In some optional embodiments, the separator may be a polypropylene (PP) film, a polyethylene (PE) film or a PP / PE / PP porous film, for example, a PP / PE / PP porous film.
[0096] Wherein, the air permeability of the diaphragm may be 180-380 s / 100mL.
[0097] Wherein, the porosity of the diaphragm may be 30%-50%.
[0098] Wherein, the thickness of the diaphragm may be 9-18 μm.
[0099] In a specific embodiment, the diaphragm is a polyethylene film; the thickness of the diaphragm is 16 μm; the air permeability of the diaphragm is 230 s / 100 mL; and the porosity of the diaphragm is 40%.
[0100] Electrolyte
[0101] In some embodiments, the electrolyte may be an electrolyte conventionally used for batteries in the art, generally including a non-aqueous solvent, a lithium salt, and additives.
[0102] In some embodiments, the preparation method of the lithium-ion battery includes the following steps: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, so that the separator is located between the positive and negative electrode sheets to play an isolating role; then wrapping with an aluminum-plastic film, injecting the electrolyte after drying, and finally preparing a soft-pack battery through packaging, standing, formation and other processes.
[0103] In some embodiments, the capacity of the lithium-ion battery is, for example, 1 Ah.
[0104] Electronic devices
[0105] The electronic device provided in the third aspect of the present invention comprises the electrochemical device as described above.
[0106] Exemplarily, the electronic device described in the present invention may be, but is not limited to, mobile devices (such as mobile phones, tablet computers, laptop computers, video recorders, portable printers / copiers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems and backup power supplies, etc.
[0107] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0108] The reagents and raw materials used in the present invention are commercially available.
[0109] Example 1
[0110] The preparation of the positive electrode sheet includes the following steps:
[0111] The first positive electrode material is lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O 4 ) is mixed with a first conductive agent (SP and CNT, the mass ratio of the two is 1:0.8) and a first binder PVDF according to a mass ratio of 97.2:1.8:1, and a solvent NMP is added, and the mixture is fully stirred to obtain a first positive electrode slurry; the first positive electrode slurry is coated on a positive electrode current collector aluminum foil, and after drying, the first positive electrode slurry forms a first active material layer;
[0112] The second positive electrode material is lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O 4 ) and a second conductive agent (SP and CNT, the mass ratio of the two is 1:0.8) and a second binder PVDF are mixed in a mass ratio of 97.2:1.8:1, and a solvent NMP is added, and the mixture is fully stirred to obtain a second positive electrode slurry; the second positive electrode slurry is coated on the first active material layer, and after drying, the second positive electrode slurry forms a second active material layer; wherein the thickness of the first active material layer and the second active material layer is 35 μm (the thickness is 3.0 g / cm 3 thickness at 5000 ℃);
[0113] The positive electrode sheet is prepared through cold pressing and slitting processes.
[0114] Embodiment 2-4
[0115] The only difference between Examples 2-4 and Example 1 is that in the obtained positive electrode sheets, the average particle size of lithium nickel manganese oxide as the second positive electrode material is 1.5 μm, 1 μm or 0.5 μm, respectively, and the other conditions remain the same as in Example 1.
[0116] Embodiment 5-8
[0117] The only difference between Examples 5-8 and Example 1 is that in the obtained positive electrode sheets, the average particle size of lithium nickel manganese oxide as the first positive electrode material is 3 μm, 4 μm, 5 μm or 6 μm, respectively, and the mass ratio of the second positive electrode material, the second conductive agent and the second binder is 95.8:3.2:1, the mass ratio of SP and CNT in the second conductive agent is 2:1.2, and the other conditions are consistent with Example 1.
[0118] Example 9
[0119] The difference between Example 9 and Example 1 is that in the obtained positive electrode sheet, the first positive electrode material and the second positive electrode material are both LiNi 0.5 Mn 1.5 O 4 and lithium iron manganese phosphate (the mass ratio of the two is 95:5), and the other conditions are consistent with those in Example 1. Among them, the molecular formula of lithium iron manganese phosphate is LiMn 0.6 Fe 0.4 PO 4 The average particle size of lithium manganese iron phosphate is 0.3μm.
[0120] Example 10
[0121] The difference between Example 10 and Example 1 is that in the obtained positive electrode sheet, the first positive electrode material and the second positive electrode material are both LiNi 0.5 Mn 1.5 O 4 and lithium iron phosphate (the mass ratio of the two is 95:5, and the average particle size of the lithium iron phosphate is 1.1 μm), and the other conditions are consistent with Example 1.
[0122] Embodiment 11
[0123] The only difference between Example 11 and Example 1 is that in the obtained positive electrode sheet, the first conductive agent and the second conductive agent are both SP, and the other conditions are consistent with Example 1.
[0124] Example 12
[0125] The only difference between Example 12 and Example 11 is that in the obtained positive electrode sheet, the mass ratio of the first positive electrode material, the first conductive agent and the first binder is 97.8:1.2:1; the mass ratio of the second positive electrode material, the second conductive agent and the second binder is 96.6:2.4:1;
[0126] The remaining conditions remain the same as those in Example 1.
[0127] Embodiment 13
[0128] The only difference between Example 13 and Example 11 is that in the obtained positive electrode sheet, the mass ratio of the first positive electrode material, the first conductive agent and the first binder is 96.6:2.4:1; the mass ratio of the second positive electrode material, the second conductive agent and the second binder is 97.8:1.2:1;
[0129] The remaining conditions remain the same as those in Example 1.
[0130] Embodiment 14
[0131] The difference between Example 14 and Example 1 is that in the obtained positive electrode sheet, the thickness of the first positive electrode active layer is 35 μm, the thickness of the second positive electrode active layer is 17.5 μm, and after the second positive electrode slurry forms the second active material layer, a third active material layer is provided on the second active material layer (the thickness of the third positive electrode active layer is 17.5 μm), and the above thicknesses are all compressed to 3.0 g / cm 3 wherein the specific steps of providing the third active material layer on the second active material layer are as follows:
[0132] The third positive electrode material is lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O 4 ) is mixed with a third conductive agent (SP and CNT, the mass ratio of the two is 1:0.8) and a third binder PVDF according to a mass ratio of 97.2:1.8:1, and a solvent NMP is added, and the mixture is fully stirred to obtain a third positive electrode slurry; the third positive electrode slurry is coated on the second active material layer, and after drying, the third positive electrode slurry forms a third active material layer;
[0133] The remaining conditions remain the same as those in Example 1.
[0134] In the positive electrode sheet obtained in Example 14, the average particle sizes of lithium nickel manganese oxide in the first positive electrode active layer, the second positive electrode active layer and the third positive electrode active layer were 4 μm, 2 μm and 1 μm respectively, and the contents of the first conductive agent, the second conductive agent and the third conductive agent were all 1.8%.
[0135] The schematic diagram of the structure of the positive electrode sheet obtained in Example 1-13 is as follows Figure 1 The positive electrode sheet includes a positive electrode current collector 1, and a first active material layer 2 and a second active material layer 3 are sequentially arranged in a direction away from the positive electrode current collector 1.
[0136] Comparative Example 1
[0137] The difference between this comparative example and Example 1 is that in the obtained positive electrode sheet, the average particle size of lithium nickel manganese oxide as the first positive electrode material and the second positive electrode material is 4 μm, and the other conditions are consistent with Example 1.
[0138] Comparative Example 2
[0139] The difference between this comparative example and Example 1 is that in the obtained positive electrode sheet, the average particle size of lithium nickel manganese oxide as the first positive electrode material and the second positive electrode material is 1 μm, and the other conditions are consistent with Example 1.
[0140] Comparative Example 3
[0141] The difference between this comparative example and Example 1 is that in the obtained positive electrode sheet, the average particle size of lithium nickel manganese oxide as the first positive electrode material is 1 μm, and the average particle size of lithium nickel manganese oxide as the second positive electrode material is 4 μm;
[0142] The mass ratio of the first positive electrode material, the first conductive agent and the first binder is 95.8:3.2:1, and the mass ratio of SP and CNT in the first conductive agent is 2:1.2;
[0143] The remaining conditions remain the same as those in Example 1.
[0144] Comparative Example 4
[0145] The difference between this comparative example and Example 1 is that in the obtained positive electrode sheet, the average particle size of lithium nickel manganese oxide as the first positive electrode material and the second positive electrode material is 5 μm, and the other conditions are consistent with Example 1.
[0146] Comparative Example 5
[0147] The difference between this comparative example and Example 1 is that in the obtained positive electrode sheet, the average particle size of lithium nickel manganese oxide as the first positive electrode material and the second positive electrode material is 2 μm, and the other conditions are consistent with Example 1.
[0148] Comparative Example 6
[0149] The difference between this comparative example and Example 1 is that in the obtained positive electrode sheet, the average particle size of lithium nickel manganese oxide as the first positive electrode material is 2 μm, and the average particle size of lithium nickel manganese oxide as the second positive electrode material is 4 μm, and the other conditions are consistent with Example 1.
[0150] Comparative Example 7
[0151] The difference between this comparative example and Example 1 is that: the positive electrode sheet is prepared by the following method: the first positive electrode slurry and the second positive electrode slurry are blended to obtain a mixed positive electrode slurry, the mixed positive electrode slurry is coated on the positive electrode current collector aluminum foil, and after drying, the mixed positive electrode slurry forms a positive electrode material layer; after cold pressing and slitting steps, the positive electrode sheet is prepared;
[0152] The formula of the first positive electrode slurry and the second positive electrode slurry is the same as that of Example 1, and the total thickness of the positive electrode material layer is 70 μm (the thickness is 3.0 g / cm 3 The other conditions are the same as those in Example 1.
[0153] Some parameters of the positive electrode sheets obtained in Examples 1-13 and Comparative Examples 1-7 are shown in Table 1.
[0154] Effect Example 1
[0155] The longitudinal cross-sections of the positive electrode sheets in Examples 1-14 and Comparative Examples 1-7 were subjected to SEM testing to obtain the average particle size of lithium nickel manganese oxide in each active material layer. The specific method is as follows:
[0156] The positive electrode sheet is cut along the thickness direction of the positive electrode sheet to obtain the longitudinal section of the positive electrode sheet, and the longitudinal section is subjected to SEM test with a magnification of 5000 times to obtain the SEM image of the longitudinal section of the positive electrode sheet. A 25 μm×15 μm area is randomly selected in each active material layer in the SEM image, and the particle sizes of all lithium nickel manganese oxide particles in the area are counted, and the average value is calculated to obtain the average particle size of lithium nickel manganese oxide in the active material layer. Among them, the particle size of a single lithium nickel manganese oxide particle is the distance between the two farthest endpoints of the particle that do not overlap. When the active material layer also includes other positive electrode materials, different positive electrode material particles can be distinguished by means of EDS or other methods.
[0157] Taking Example 1 as an example, the partial SEM image of the longitudinal cross section of the obtained positive electrode sheet is as follows: Figure 2 It should be noted that Figure 2 The particle size statistics method of lithium nickel manganese oxide is only exemplified.
[0158] Effect Example 2
[0159] 1. Preparation of lithium-ion soft-pack batteries
[0160] (1) Preparation of negative electrode
[0161] The negative electrode material artificial graphite, the conductive agent acetylene black, the thickener CMC, and the binder SBR are mixed in a mass ratio of 96.4: 1:1.2:1.4, and the solvent deionized water is added, and the mixture is fully stirred to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode collector copper foil, and the negative electrode sheet is prepared through drying, cold pressing, and slitting processes.
[0162] (2) Preparation of electrolyte
[0163] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF 6 Dissolve in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0164] (3) Diaphragm
[0165] A PP / PE / PP porous membrane with a thickness of 16 μm was used as the separator.
[0166] Among them, the air permeability of the membrane is 230 s / 100mL and the porosity is 40%.
[0167] (4) Assembly of lithium-ion batteries
[0168] The positive electrode sheets in Examples 1-14 and Comparative Examples 1-7 are respectively used to assemble lithium-ion batteries, and the specific steps are as follows:
[0169] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in sequence, so that the separator is placed between the positive and negative electrode sheets to play a role of isolation. Then, the aluminum plastic film is wrapped, and after drying, the above-prepared electrolyte is injected. After packaging, standing, and forming, a soft-pack battery with a capacity of 1 Ah, that is, a lithium-ion battery, is finally prepared.
[0170] 2. Performance test of lithium-ion batteries
[0171] (1) 3C / 0.33C discharge capacity retention rate:
[0172] The lithium-ion battery is cycled at 0.33C for 3 cycles between 3.5-4.9V; the discharge capacity of the 3rd cycle is C 1 The lithium-ion battery was fully charged at 0.33C rate, left to stand for 30 minutes, and then discharged at 3C rate to 3.5V. The discharge capacity was recorded as C 2 , C 2 / C 1 That is the 3C / 0.33C discharge capacity retention rate.
[0173] (2) DCR: The lithium-ion battery is adjusted to 50% SOC and the DCR is tested at 4C discharge for 30 seconds.
[0174] (3) High temperature gas production performance
[0175] After fully charging the lithium-ion battery, test the initial volume V 1 Then, store it in a high temperature cabinet at 60℃, recharge it and test its volume every 7 days. After 30 days, the volume is V 2 , (V 2 -V 1 ) / V 1 ×100% is the high-temperature gas production growth rate.
[0176] The above test results are shown in Table 2.
[0177]
[0178]
[0179] As can be seen from Tables 1 and 2, the average particle size of lithium nickel manganese oxide in the positive electrode sheet based on lithium nickel manganese oxide of the present invention decreases in sequence along the direction away from the positive electrode current collector, and the lithium ion battery prepared using the positive electrode sheet has low impedance and low high-temperature gas production growth, which can take into account excellent high-temperature performance and kinetic performance. Specifically, the high-temperature gas production growth rate of the lithium ion battery can be less than 30% after 30 days, the 3C / 0.33C discharge capacity retention rate can reach more than 40%, and the DCR at 50% SOC can be less than 132Ω.
[0180] However, when only lithium nickel manganese oxide with the same average particle size is used, whether it is lithium nickel manganese oxide with a large average particle size or a small average particle size, or the average particle size of lithium nickel manganese oxide increases successively in the direction away from the positive electrode current collector, or lithium nickel manganese oxide with large and small average particle sizes is simply mixed, the resulting positive electrode sheet cannot achieve the above effect. This may be because reducing the average particle size of lithium nickel manganese oxide as the second positive electrode material is beneficial to improving the electrode sheet dynamics and reducing DCR. Compared with the single-layer coating design, the double-layer gradient coating of the upper and lower electrodes can significantly improve the dynamics, and the high-temperature gas production performance deteriorates less.
[0181] Compared with Example 1, the two active material layers in Comparative Example 1 both use lithium nickel manganese oxide with the same and larger average particle size. Although the resulting lithium-ion battery has a relatively excellent high-temperature gas production growth rate after 30 days, the 3C / 0.33C discharge capacity retention rate and the DCR at 50% SOC are significantly deteriorated and cannot be taken into account.
[0182] Compared with Example 7, the two active material layers in Comparative Example 4 both use lithium nickel manganese oxide with the same and larger average particle size. Although the high-temperature gas production growth rate of the resulting lithium-ion battery after 30 days is low, the 3C / 0.33C discharge capacity retention rate and the DCR at 50% SOC are greatly deteriorated.
[0183] Compared with Example 3, the two active material layers in Comparative Example 2 both use lithium nickel manganese oxide with the same smaller average particle size. Although the 3C / 0.33C discharge capacity retention rate and DCR at 50% SOC of the lithium-ion battery are relatively excellent, the high-temperature gas production growth rate after 30 days is significantly improved.
[0184] Compared with Example 1, the two active material layers in Comparative Example 5 both use lithium nickel manganese oxide with the same smaller average particle size. Although the 3C / 0.33C discharge capacity retention rate of the lithium-ion battery is equivalent to the DCR at 50% SOC, the high-temperature gas production growth rate after 30 days is significantly worse.
[0185] Compared with Example 6, the average particle size of lithium nickel manganese oxide in the positive electrode sheet of Comparative Example 3 increases successively along the direction away from the positive electrode current collector. Although the growth rate of high-temperature gas production of the lithium-ion battery after 30 days is low, the 3C / 0.33C discharge capacity retention rate and the DCR at 50% SOC are significantly deteriorated.
[0186] Compared with Example 1, the average particle size of lithium nickel manganese oxide in the positive electrode sheet of Comparative Example 6 increases successively along the direction away from the positive electrode current collector. Although the growth rate of high-temperature gas production of the lithium-ion battery after 30 days is low, the 3C / 0.33C discharge capacity retention rate and the DCR at 50% SOC are greatly deteriorated.
[0187] Compared with Example 1, in Comparative Example 7, the first positive electrode slurry and the second positive electrode slurry including lithium nickel manganese oxide with large and small average particle sizes were simply directly mixed to obtain a positive electrode sheet with only a single layer of active material layer. The high-temperature gas production growth rate of the prepared lithium-ion battery increased after 30 days, the 3C / 0.33C discharge capacity retention rate decreased, and the DCR at 50% SOC was significantly increased.
[0188] By comparing Examples 3 and 6, it can be found that by increasing the content of the second conductive agent so that the content of the second conductive agent is greater than that of the first conductive agent, the DCR can be further reduced and the kinetics can be improved without losing the high-temperature gas production performance.
[0189] It should be noted that: although the above-mentioned embodiments of the present invention do not reflect the situation where the nickel manganese oxide contains doping elements M (which may include one or more of Co, Mg, Al, Cu, Ta, Zr, Ti and Ca), in fact, the lithium nickel manganese oxide containing the above-mentioned doping elements is still applicable to the technical scheme of the present invention and can achieve the technical effects of the present invention.
[0190] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A positive electrode sheet, characterized in that: It includes a positive electrode current collector and a positive electrode material layer, wherein the positive electrode material layer is arranged on at least one surface of the positive electrode current collector; the positive electrode material layer includes at least two active material layers; the positive electrode material in each active material layer includes lithium nickel manganese oxide; the average particle size of the lithium nickel manganese oxide in each active material layer decreases successively along the direction away from the positive electrode current collector.
2. The positive electrode sheet according to claim 1, characterized in that: The active material layer further includes a conductive agent, and the content of the conductive agent in each active material layer increases gradually along a direction away from the positive electrode current collector.
3. The positive electrode sheet according to claim 1, characterized in that: The positive electrode material layer satisfies one or more of the following conditions ad: a. The positive electrode materials in each active material layer independently include one or both of lithium iron manganese phosphate and lithium iron phosphate; b. Along the direction away from the positive electrode current collector, the ratio of the average particle sizes of lithium nickel manganese oxide in two adjacent active material layers is (1.5-20): 1; c. The content of lithium nickel manganese oxide in each active material layer is greater than or equal to 80%; d. The total thickness of the positive electrode material layer is 10-100 μm.
4. The positive electrode sheet according to claim 1, characterized in that: The positive electrode material layer comprises two active material layers, which are a first active material layer and a second active material layer in a direction away from the positive electrode current collector; The first active material layer includes a first positive electrode material; and the second active material layer includes a second positive electrode material.
5. The positive electrode sheet according to claim 4, characterized in that: The positive electrode material layer satisfies one or more of the following conditions ad: a. The average particle size of lithium nickel manganese oxide in the first positive electrode material is 3-6 μm; b. The average particle size of lithium nickel manganese oxide in the second positive electrode material is 0.5-2 μm; c. In the first active material layer, the content of the first positive electrode material is 80%-99%; d. In the second active material layer, the content of the second positive electrode material is 80%-99%.
6. The positive electrode sheet according to claim 4, characterized in that: The first active material layer includes a first conductive agent, the second active material layer includes a second conductive agent, and the first conductive agent and the second conductive agent satisfy one or more of the following conditions ad: a. The content of the first conductive agent is the same as the content of the second conductive agent; or, the content of the first conductive agent is less than the content of the second conductive agent; b. The mass ratio of the first conductive agent to the second conductive agent is 1:(0.5-3); c. The content of the first conductive agent is 1.8%-3.2%; d. The content of the second conductive agent is 1.8%-3.2%.
7. The positive electrode sheet according to claim 4, characterized in that: The thickness ratio of the first active material layer to the second active material layer is 1:(0.5-10).
8. An electrochemical device, characterized in that: It comprises the positive electrode sheet as described in any one of claims 1 to 7.
9. The electrochemical device according to claim 8, characterized in that The electrochemical device is a lithium ion battery.
10. An electronic device, characterized in that: It comprises the electrochemical device as claimed in claim 8 or 9.
Citation Information
Patent Citations
Positive electrode plate and lithium ion battery
CN110660961A
Pole piece, electrochemical device and electronic device
CN112802990A
Battery
CN113258031A
Lithium ion battery
CN113380979A
Thick electrode and preparation method and application thereof
CN115425175A
Cited By
Positive plate, battery comprising positive plate and electric device
CN120300128A